A Real-Time Prediction Method for Heat Flux in Continuous Casting Mold with Optical Fibers - Jin, Yonggang; Luo, Sen; Meng, Xiaoliang; Liu, Zhiyuan; Wang, Chongjun; Wang, Weiling; Zhu, Miaoyong (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2025)
The heat flux is a very important indicator of primary cooling in the continuous casting mold and has a close relationship with the strand quality. Recently, the optical fiber-based sensors have great potential for temperature measurements in continuous casting mold, due to the advantages of dense measurement points, immunity to electromagnetic interference, high resolution, and so on. In this paper, a mathematical model for the inverse heat conduction problem (IHCP) is developed to determine the real-time heat flux based on measured temperature from optical fibers. The model is solved using the modified Levenberg–Marquardt (LM) algorithm that introduces the thermal difference proportionality coefficient, denoted as K t . K t represents the degree of change in temperature of two points on the copper plate when the heat flux changes. The value of K t is determined using the classical LM algorithm. Moreover, the modified LM algorithm is verified based on the temperature data measured by optical fibers. Finally, the calculation error and calculation time between the modified LM algorithm and the classical LM algorithm are compared. The results indicate that the modified LM algorithm exhibits superior calculation accuracy compared to the classical LM algorithm, with an error of less than 2 pct. Additionally, the calculation time is significantly reduced, remaining within 2 seconds. Thus, the present modified LM algorithm has a great application prospect in real-time prediction of heat flux in continuous casting mold with copper mold temperature measurements by optical fibers.